2016
DOI: 10.18632/oncotarget.14075
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a synonymous variant in TRIM59 gene for gastric cancer risk in a Chinese population

Abstract: Tripartite motif 59 (TRIM59) is a novel oncogenic driver in gastric cancer (GC) that is implicated in disease progression as well as dismal survival. Genetic variants in peculiar gene are likely candidates for conferring hereditary susceptibility. The role of TRIM59 polymorphism in predicting the risk of malignant diseases and its relevance to TRIM59 expression have not been discussed. Using a HapMap tagSNPs approach, we screened three tag TRIM59 single nucleotide polymorphisms (SNPs) (rs1141023G>A, rs7629A>G,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…The present study indicates that TRIM59 promotes CRC progression, which is similar to previous studies in other cancer types such as NSCLC (10), gastric cancer (9,21), renal cell carcinoma (11) and osteosarcoma (22). Significantly shortened survival is seen in patients with high TRIM59 expression compared with those with low TRIM59 expression.…”
Section: Discussionsupporting
confidence: 89%
“…The present study indicates that TRIM59 promotes CRC progression, which is similar to previous studies in other cancer types such as NSCLC (10), gastric cancer (9,21), renal cell carcinoma (11) and osteosarcoma (22). Significantly shortened survival is seen in patients with high TRIM59 expression compared with those with low TRIM59 expression.…”
Section: Discussionsupporting
confidence: 89%
“…p53 plays a vital role in the regulation if cell cycle transition, checkpoint activation, and apoptotic machinery in tumor cells, which control expression of p21 and p27 . It has been reported that TRIM59, as an E3 ubiquitin ligases, was able to interacted with p53, increasing its ubiquitination and degradation in gastric cancer cells . In osteosarcoma, TRIM59 could downregulate p53 in both U2OS and MG63 cells .…”
Section: Discussionmentioning
confidence: 95%
“…[25][26][27] It has been reported that TRIM59, as an E3 ubiquitin ligases, was able to interacted with p53, increasing its ubiquitination and degradation in gastric cancer cells. 28 In osteosarcoma, TRIM59 could downregulate p53 in both U2OS and MG63 cells. 29 However, knocked down TRIM59 did not upregulate p53 protein expression in lung cancer cells, suggesting its effect may be cell context dependent.…”
Section: Trim59 Activates Akt Signaling and Promotes P53 Ubiquitinamentioning
confidence: 97%
“…The occurrence and development of GC are influenced by a series of complex factors involving host genetic susceptibility and multiple environmental factors [ 3 ]. In previous epidemiological studies, several genetic polymorphisms were identified to impact the risk of GC [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%